Phytochemical determination of the leaves and roots of annona stenophylla(muloolo tree) with claimed uterotonic effect from monze west southern province - Banda David (Lusaka, the university of Zambia, school of medicine, 2016)
Phytochemicals are biologically active compounds presents in plants used for food and medicine. The medicinal value of these plants is due to phytochemicals. Annona stenophylla is one of the plants used as food and medicine.
A dissertation submitted in partial fulfilment for the award of bachelor of pharmacy at the university of Zambia.
Keywords: Medicinal plants